Global Salafism: Islam’s New Religious Movement By Roel Meijer, ed. (New York: Oxford University Press, 2013. 463 pages.) (American Journal of Islam and Society, 2014)
Roel Meijer’s edited Global Salafism: Islam’s New Religious Movement, oneof the first collected works to broadly analyze contemporary Salafism as aglobal religious movement for English-speaking audiences, presents thismovement as a string of methods for approaching Islam’s canonical sources.Its many methodological ambiguities and tactical classifications enable it toincorporate a variety of local and international religious groups: those that rejectpolitical participation (e.g., “Scholastic Salafis”), embrace their society’sestablished political rules (e.g., “Sahwah Movement”), and seek radical transformationoften through violent means (e.g., “al-Qaeda”). In part, Salafismsymbolizes a varied scholarly attempt to disentangle long-simmering questionsabout conservative forms of Muslim activism, most of which concernthe ethics of how Muslims are to conduct their lives, perceive their individualand group identities, and understand the pious order of political and socialarrangements.The volume has two primary goals: (1) to reveal the diversity among themovement’s various groups and streams and (2) to reclaim the study ofSalafism from the field of security studies, which has, since 2001, influencedmuch of our overall understanding of this rather new religious phenomenon.The contributors challenge the widespread notion of Salafism as an exclusivelyviolent and intransigent Islamic movement by addressing the tensionsbetween basic Salafi doctrines (e.g., scriptural literalism, a sharp distinctionbetween in- and outsiders, and an active program for individual and communalreform), its supposed attraction to growing numbers of Muslims, and its intrinsiclinks to politics as well as to violence. The contributors argue that thesetensions have produced a whole range of consequences for primarily Muslim ...